The Aplication of Group Investigation Based Realistic Mathematic Education Learning Model to Increase Activity and Mathematics Learnings Outcomes - umar umar; Tri Novita Irawati; Fury Styo Siskawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
Abstrack This study aims to describe the application of realistic mathematics education based on group investigative learning model for student activities and learning outcomes. The type of the research is classroom action research (CAR). Researchers conducted observations in class X APH SMK Negeri 8 Jember and obtained data on an increase in activity and student learning outcomes from cycle I to cycle II. The research design refers to the Hopskins cycle design model. Based on the research results, it was seen that there was an increase in the proportion of student learning activities, namely 51% in cycle I and 60% in cycle II. Meanwhile, for student learning outcomes, the percentage was 16% in cycle I and 78% in cycle II. After comparing between cycle I and cycle II, it can be seen that an increase in learning outcomes is as expected, namely at least 75%. This proves that the activity and student learning outcomes can be increased by the application of a group investigative learning model based on realistic mathematics education. Keywords: group investigation, realistic mathematics education, learning outcomes